Electrical Conductivity Studies of Conducting Polymer Nanocomposites in Ambient Conditions. Issue 4 (May 2016) - Ansari, Shahid Pervez; Mohammad, Faiz
Nanocomposites of conducting polymer (polyaniline, PANI) nanoparticles with zinc oxide (ZnO) nanoparticles as inorganic filler and cellulose acetate (CA) as supporting matrix were prepared by a solution-casting method using N-methyl-2-pyrrolidone (NMP) as solvent. The nanocomposites were studied for their DC electrical conductivity and stability in terms of electrical conductivity retention by isothermal accelerated ageing and cyclic accelerated ageing techniques using a four-in-line probe instrument. The nanocomposites were also characterized by FTIR, SEM, TEM, TGA and XRD. All the nanocomposite formulations followed an Arrhenius-type temperature dependence of electrical conductivity, which supported a semiconducting nature for their HCl doped state. The electrical conductivity of the as-prepared HCl doped nanocomposites was also found to be in the semiconducting region. The studied nanocomposite formulations showed good stability towards retention of their electrical conductivity up to 90°C. X-ray diffractometry (XRD) data suggested the uniform incorporation of zinc oxide nanoparticles in the polymer matrix.